NATIONAL PAYMENT SYSTEM ORGANIZATION AND DEVELOPMENT FUNDAMENTALS - E. V. Zaytseva (Модернизация, инновация, развитие)
Rapid development of national payment systems (NPS) is determined with such main factors as globalization of economic relations, application of newest information technologies, structural changes in the banking sphere and growth of the role of central banks. NPS should be considered as integral functional and institutional component of the country’s monetary system. Among main criteria that determine NPS development possibility there are its integrity, stability and flexibility. NPS may be regarded at as structure composed of the basic, organizational and regulating blocks.